Signaling Pathways Involved in Diabetic Renal Fibrosis - Zhang, Yuqing; Jin, De; Kang, Xiaomin; Zhou, Rongrong; Sun, Yuting; Lian, Fengmei; Tong, Xiaolin (Frontiers in Cell and Developmental Biology, 2021)
Diabetic kidney disease (DKD), as the most common complication of diabetes mellitus (DM), is the major cause of end-stage renal disease (ESRD). Renal interstitial fibrosis is a crucial metabolic change in the late stage of DKD, which is always considered to be complex and irreversible. In this review, we discuss the pathological mechanisms of diabetic renal fibrosis and discussed some signaling pathways that are closely related to it, such as TGF-β, MAPK, Wnt/β-catenin, PI3K/Akt, JAK/STAT, and Notch pathway. The cross-talks among these pathways were then discussed to elucidate the complicated cascade behind the tubulointerstitial fibrosis. Finally, we summarized the new drugs with potential therapeutic effects on renal fibrosis and listed related clinical trials. The purpose of this review is to elucidate the mechanisms and related pathways of renal fibrosis in DKD and to provide novel therapeutic intervention insights for clinical research to delay the progression of renal fibrosis.